Opportunities, challenges, and implications of social media in Indonesian language learning in the digital era: Systematic literature review - Sakinah Isna Firmani (DRPM UNY, 2026)
The use of social media has been widely adopted by various groups, including teachers and students, in the learning process. This study aims to comprehensively explore the opportunities, challenges, and implications of using social media in Indonesian language learning in the digital era. This research employed the Systematic Literature Review (SLR) method by referring to the PRISMA 2020 model. Based on the selection process, eight articles were identified and further analyzed through the Systematic Literature Review (SLR) technique regarding the opportunities, challenges, and implications of social media in Indonesian language learning in the digital era. The findings indicate that the utilization of social media has proven effective in enhancing students’ motivation, active engagement, creativity, and learning outcomes at various educational levels. However, the effectiveness of social media use largely depends on teachers’ digital literacy readiness and well-planned management. Therefore, the successful integration of social media requires systematic planning, starting from setting objectives to evaluation, as well as improving teachers’ competencies in order to provide learning that is directed, safe, and educational.